PEMANFAATAN MIKROBA AUTOTROPH DALAM PENGOLAHAN LIMBAH NITRAT KONSENTRASI TINGGI - Rudi Nugroho (Jurnal Teknologi Lingkungan, 2003)
The treatment of wastewater containing high concentration of nitrate and lowconcentration of BOD using autotrophic bacteria were conducted in batchsuspension experiment to investigate nitrate concentration level which can betreated by the bacteria. The autotrophic bacteria were enriched by acclimatingactivated sludge with inorganic substrates. The experimental result shows thatdenitrification reaction with initial nitrate concentration in synthetic wastewater from 200 to 850 mg/l proceeded according to the one-order reaction. The denitrification rate increased with increasing the initial nitrate concentration. Sulfate was detected as the by product of the denitrification reaction. The sulfate produced for 1 mmol of nitrate decreased was 1.09 mmol.